Encapsulating peritoneal sclerosis in a young cat. Issue 1 (4th January 2018) - Sonck, Laurien; Chiers, Koen; Ducatelle, Richard; Van Brantegem, Leen
Abstract : A 10‐month‐old female Maine Coon was presented with repeated vomiting, abdominal distension and lethargy. Clinical examination, ultrasound and radiography revealed a copious amount of serohemorrhagic ascites accompanied with dorsal displacement of clustered small intestinal loops and a liver with rounded edges. On exploratory coeliotomy, the abdominal organs were small and poorly discernible. They were covered by a severely thickened peritoneum which caused an abnormal organ shape due to a scar‐like contraction of the organ's capsule. Given the severe clinical signs, the chronic and severe appearance on exploratory coeliotomy, as well as the inability to remove the layer, the animal was euthanased. Gross and histological examinations demonstrated a diffuse fibrotic serosa with involvement of all abdominal organs. The condition was diagnosed as encapsulating peritoneal sclerosis grade 3. This is a rare, chronic inflammatory disease transforming the peritoneum into a thick, sclerotic layer. The disease usually presents as a partial intestinal obstruction.